1996
DOI: 10.1159/000106886
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolic Changes in Alzheimer's Disease: Neurobehavioral Patterns

Abstract: Regional cerebral glucose metabolism was surveyed in 37 Alzheimer''s disease (AD) patients and 21 normal controls using positron emission tomography. Where possible, brain regions were specified according to their neurobehavioral function rather than as anatomically demarcated structures. Absolute metabolic values revealed significant differences (p < 0.05) between AD patients and controls for whole brain and the more superior supratentorial brain slices. Normalized values (region/brain stem) showed the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…4,8,9,[21][22][23] We did not find any GM volumetric differences in the sensorimotor and visual cortices, consistent with previously published reports. 24,25 GM volume reductions were not found in the lower parietal, cingulate or precuneus areas, even in patients with a CDR score of 2, possibly due to the recruitment of patients over 60 years of age with late-onset AD. One previous study found that patients with early-onset AD showed bilateral reductions in the medial temporal lobes, inferior parietal lobules, the precuneus and perisylvian cortices, the right inferior frontal gyrus and bilaterally in the cingulate cortices, whereas late-onset patients with AD showed atrophy in only the bilateral medial temporal cortices.…”
Section: Discussionmentioning
confidence: 88%
“…4,8,9,[21][22][23] We did not find any GM volumetric differences in the sensorimotor and visual cortices, consistent with previously published reports. 24,25 GM volume reductions were not found in the lower parietal, cingulate or precuneus areas, even in patients with a CDR score of 2, possibly due to the recruitment of patients over 60 years of age with late-onset AD. One previous study found that patients with early-onset AD showed bilateral reductions in the medial temporal lobes, inferior parietal lobules, the precuneus and perisylvian cortices, the right inferior frontal gyrus and bilaterally in the cingulate cortices, whereas late-onset patients with AD showed atrophy in only the bilateral medial temporal cortices.…”
Section: Discussionmentioning
confidence: 88%
“…For example, a decreased density of glucose transporter sites supports the last assumption and suggests reduced glucose availability in the affected brain regions 5–7. Hence, the imposed metabolic crisis may be reflected by data indicating decreased cerebral glucose uptake and oxygen utilization in Alzheimer brains 8–10…”
Section: Introductionmentioning
confidence: 77%
“…Mitochondrial abnormalities appear to lead to the energy failure and defective energy metabolism fundamental to AD pathology 46,48‐52,56,90,91. Presently, it is widely accepted that the metabolic defects and vascular abnormalities in AD appear to reduce brain metabolism and are correlated with the severity of AD 1,2,4,6,50,54,56,90–93. For the present study, we have extended our investigation to include the vascular compartment.…”
Section: Resultsmentioning
confidence: 99%